A vantagem dos míopes: entre história e literatura (Studia Iberystyczne, 2014)
THE ADVANTAGE OF THE SHORT-SIGHTED: BETWEEN HISTORY AND LITERATUREThrough a brief presentation of some culturally specific aspects of the process of development of the Brazilian intellectual life, this paper seeks to shed new light on the concept of auditivity, considered fundamental for the study of the complex relationships between literature and history in Brazil. From this perspective, the autonarrative fiction with memory feature should be seized as an alternative to historical discourse, since it declares its own fictionality and the limitations of its own narrative focus, and therefore is capable of avoiding the globalizing claims that in the case of heterogeneous Brazilian society appear to be inappropriate.